The Effect of Sawdust Concentration on Biogas Production from Chicken Dung in Anaerobic Co-Digestion - Budiyono Budiyono; Andrew Christian Timothy Prasetyo; Grace Sheilla Kristiani Handoko; Hashfi Hawali Abdul Matin (Waste Technology, 2022)
Resources of oil and natural gas which are derived from fossil energy are wane more and more. One of the research of alternative energy are the production of biogas. Biogas is formed when organic material is degraded by microorganisms in anerobic conditions. Biogas consists of methane gas (50-70%), carbon dioxide (30-50%), and also includes small amounts of other compounds such as hydrogen sulfide (H2S), nitrogen gas (N2) and water vapor. The purpose of this study is to examine the effect of pretreatment on the biogas yield produced, examine the effect of adding nutrients to the biogas yield produced, and examine the effect of the C/N ratio value on the biogas yield produced. Anaerobic fermentation is a series of biological processes that convert organic matter into CH4 and CO2 and also convert S compounds to H2S in the absence of oxygen (O2) by anaerobic microorganisms consisting of four primary stages. In biogas production research, the variables used are the C/N ratio, pretreatment of raw materials, and the addition of nutrients. This research includes three processes, there are the preparation process, the operation process, and the result analysis. It is known that chemical pretreatment using acids results in greater biogas products. Then, the results were obtained that biogas with C/N 30 produced more biogas products. The liquid state (L-AD) method produces more biogas than the solid state (SS-AD) method. The HCl pretreatment variable with C/N ratio of 30, and TS 10% produces the largest kinetics rate compared to other variables.